Developing a curriculum content for children’s character development based on Tahdhib Al-Akhlaq Wa Tathir Al-A’raq and Ihya’ ‘Ulūm Al-Din / Asmaa’ Mohd. Arshad - Mohd. Arshad, Asmaa’ (2009)

(untitled)
This research aims at developing a Curriculum Content for Children’s Character Development module proposed for parent education programs in Malaysia. The proposed curriculum content is focusing on a character development module for the Malay-Muslims youth who are currently suffering from a severe crises of character. For this purpose, the curriculum content is developed based on the content analysis of two selected Arabic texts derived from: Kitāb Tahdhīb al-Akhlāq wa Tathīr al-A‘rāq written by Ibn Miskawayh and Kitāb Ihyā’ ‘Ulūm al-Dīn written by Abu Hamid Muhammad al-Ghazali. Based on the content analysis of both selected texts, a Curriculum Content for Children’s Character Development is developed and further evaluated. Therefore, data analysis is divided into two phases of research: Phase One: Content Analysis Research Phase Two: Curriculum Evaluation In the first phase of this research (Phase One), the researcher analyzes the selected texts using a qualitative semantic analysis approach. In this case, the researcher is using a non-frequency qualitative method due to the need for analyzing the conceptual framework, the contexts and latent understanding of the texts. For this purpose, the content analysis of these selected texts highlights the similarities of Ibn Miskawayh and al-Ghazali’s views concerning the Objectives of Character Education and the Curriculum Content for Children’s Character Development. In the second phase of this research (Phase Two), the proposed Objectives of Character Education and the Curriculum Content are further implemented and evaluated in order to assess its feasibility. ii In the Curriculum Evaluation process, the proposed curriculum content is implemented as one of the modules for CCL 2052: Family Management and Parenting Course in IIUM. Respondents’ feedbacks before and after the curriculum implementation (pre and post evaluation) are recorded and analyzed. Congruence of the pre and post-evaluation analysis are comparatively analyzed. Based on the Congruence Analysis of pre and post-evaluation exercise, the curriculum content is further refined and developed into a final proposal. It is hoped that the proposed Curriculum Content for Children’s Character Development will be realized and implemented for the benefit of the Malay-Muslim parents in Malaysia. It is also hoped that some of these research findings will serve the needs of Malaysia as a developing nation. In the transformation process towards a developed nation, Malaysia is currently facing critical challenges of human development. One of the most critical challenges of 2020 Vision is how to create a moral society imbued with high ethical and religious values, that evenly balanced with the physical development. Last but not least, the importance of familial stability and parental leadership in developing children’s character and identity are basic premises of human development.